Current Practices of Electroconvulsive Therapy in Mental Disorders: A Systematic Review and Meta-Analysis of Short and Long-Term Cognitive Effects. Issue 2 (June 2021) - Landry, Marilyne; Moreno, Alexander; Patry, Simon; Potvin, Stephane; Lemasson, Morgane
Abstract : Abstract: Electroconvulsive therapy (ECT) remains one of the most effective treatments for major depressive disorder, but uncertainties persist regarding the cognitive tests to include in ECT follow-up. The current study is a systematic review and meta-analysis of the most frequent cognitive side effects after ECT. We also discuss the most common cognitive tests in ECT follow-up. We searched studies published from 2000 to 2017 in English and French language in Pubmed, EBM Reviews, EMBASE, and PsycINFO. Standardized cognitive tests were separated into 11 cognitive domains. Comparisons between cognitive measures included pre-ECT baseline with post-ECT measures at 3 times: PO1, immediately post-ECT (within 24 hours after last ECT); PO2, short term (1–28 days); and PO3, long term (more than 1 month). A total of 91 studies were included, with an aggregated sample of 3762 individuals. We found no significant changes in global cognition with Mini-Mental State Examination at PO1. Hedges g revealed small to medium effect sizes at PO2, with individuals presenting a decrease in autobiographical memory, verbal fluency, and verbal memory. Verbal fluency problems showed an inverse correlation with age, with younger adults showing greater deficits. At PO3, there is an improvement on almost all cognitive domains, including verbal fluency and verbal memory. There is a lack of standardization in the choice of cognitive tests and optimal cognitive timing. The Mini-Mental State Examination is the most common screening test used in ECT, but its clinical utility is extremely limited to track post-ECT cognitive changes. Cognitive assessment for ECT purposes should include autobiographical memory, verbal fluency, and verbal memory. Abstract : Supplemental digital content is available in the text.